Encyclopaedia of religion and ethics; index vol. - Hastings, James 1852-1922; Selbie, John A. (Edinburgh, Scotland T and T Clark, 1926)
Contents : index volume for entire set of encyclopaedias.
Keywords: Religion -- Ethics